(untitled) (Hoboken, N.J., 2006)
This book covers both recent advances in the design and synthesis of new drugs, as well as the myriad other issues facing a new drug candidate as it moves through the development process. Utilizing recent case studies, the authors provide valuable insights into the complexities of the process, from designing new synthetic methodologies and applying new automated techniques for finding optimal reaction conditions to selecting the final drug form and formulation.
Keywords: Clinical pharmacology,Pharmaceutical technology,Dược lý lâm sàng,Công nghệ dược phẩm